Integrable formulation of the OPE coefficients in the UV limit of the sine-Gordon model - Árpád Hegedűs (Journal of High Energy Physics)
Abstract In the repulsive regime of the sine-Gordon model, we work out a method, that enables one to formulate the UV limit of finite volume expectation values in terms of the integrable description of the UV limit of the corresponding spectral problem. Since these expectation values are related to 3-point couplings containing at least two identical operators, our computations provide with an integrable formulation to the 3-point couplings of the UV CFT. Our approach is based on the fermionic description of operators in the sine-Gordon theory, in which these expectation values are expressed in terms of a finite number of elements of an infinite matrix. Focusing on vacuum expectation values, in this paper, the first two nontrivial coefficients in the UV series representation of this matrix are expressed in terms of integrability data. This allows one to get an integrable description to some specific ratios of vacuum expectation values in the complex Liouville CFT.